Sex-specific prognostic value of automated epicardial adipose tissue quantification on serial lung cancer screening chest computed tomography - Brendel, Jan Michael; Mayrhofer, Thomas; Hadzic, Ibrahim; Norton, Emilia; Langenbach, Isabel L; Langenbach, Marcel C; Jung, Matthias; Raghu, Vineet K; Nikolaou, Konstantin; Douglas, Pamela S; Lu, Michael T; Aerts, Hugo J W L; et al. (European heart journal - cardiovascular imaging, 2025)
Epicardial adipose tissue (EAT) is a metabolically active fat depot associated with coronary atherosclerosis and cardiovascular (CV) risk. While EAT is a known prognostic marker in lung cancer screening, its sex-specific prognostic value remains unclear. This study investigated sex differences in the prognostic utility of serial EAT measurements on low-dose chest computed tomography (CT).We analysed baseline and 2-year changes in EAT volume and density using a validated automated deep-learning algorithm in 24 008 heavy-smoking participants from the National Lung Screening Trial (NLST). Sex-stratified multivariable Cox models, adjusted for CV risk factors, body mass index (BMI), and coronary artery calcium (CAC), assessed associations between EAT and all-cause and CV mortality [median follow-up 12.3 years (IQR: 11.9-12.8), 4668 (19.4%) all-cause deaths, 1083 (4.5%) CV deaths]. Women (n = 9841; 41%) were younger, with fewer CV risk factors, lower BMI, fewer pack-years, and lower CAC than men (all P < 0.001). Baseline EAT was associated with similar all-cause and CV mortality risk in both sexes [max. aHR women: 1.70; 95% confidence interval (CI): 1.13-2.55; men: 1.83; 95% CI: 1.40-2.40, P-interaction = 0.986]. However, 2-year EAT changes predicted CV death only in women (aHR: 1.82; 95% CI: 1.37-2.49; P < 0.001), and showed a stronger association with all-cause mortality in women (aHR: 1.52; 95% CI: 1.31-1.77) than in men (aHR: 1.26; 95% CI: 1.13-1.40; P-interaction = 0.041).In this large lung cancer screening cohort, serial EAT changes independently predicted CV mortality in women and were more strongly associated with all-cause mortality in women than in men. These findings support routine EAT quantification on chest CT for improved sex-specific cardiovascular risk stratification.
Gesehen am 13.10.2025